Comparison of 0.2% ropivacaine, 0.125% bupivacaine, and 0.25% bupivacaine for duration and magnitude of action in peripheral arterial blood flow induced by sympathetic block in dogs. Issue 5 (1st September 2004) - Takahashi, Yoshiyuki; Yamaguchi, Shigeki; Tezuka, Masatomo; Kimura, Yoshiyuki; Nagao, Masaru; Yamazaki, Hajime; Hamaguchi, Shinsuke
Abstract : Background and objectives: The aim of this study is to compare 0.2% ropivacaine with 0.125% bupivacaine or 0.25% bupivacaine for the duration and magnitude of the vasodilation effect induced by sympathetic block. Methods: We measured mean arterial pressure, heart rate, and right and left brachial artery blood flow (BABF) before and after cervicothoracic sympathetic block in 24 dogs. The experimental protocol was designed as follows: (1) left cervicothoracic sympathetic block with 1.0 mL 0.2% ropivacaine (n = 8), (2) left cervicothoracic sympathetic block with 1.0 mL 0.125% bupivacaine (n = 8), and (3) left cervicothoracic sympathetic block with 1.0 mL 0.25% bupivacaine (n = 8). Results: Mean arterial pressure and heart rate did not change significantly throughout the study in either group. Left cervicothoracic sympathetic block with 0.2% ropivacaine increased left BABF significantly from 5 to 100 minutes after the block (baseline, 100%; peak at 10 minutes after the block, 254 ± 38%; P < .01). Left cervicothoracic sympathetic block with 0.125% bupivacaine increased left BABF significantly from 5 to 80 minutes after the block (baseline, 100%; peak at 10 minutes after the block, 144 ± 9%; P < .01). Left cervicothoracic sympathetic block with 0.25% bupivacaine increased left BABF significantly from 5 to 100 minutes after the block (baseline, 100%; peak at 10 minutes after the block, 235 ± 61%; P <.01). Conclusion: Ropivacaine may be equally potent to bupivacaine at equal concentrations in sympathetic block in dogs.